ASOSIASI WACANA “ALUN-ALUN SERIBU PATUNG” DENGAN SITUASI POLITIK KEBANGSAAN DI INDONESIA PADA MASA DAN PASCAREFORMASI - Natal P. Sitanggang (Balai Bahasa Provinsi Bali, 2018)
From a linguistic point of view, short stories are classified into the type of discourse. Therefore, the tracing of everything on the authors’ intentions can be done through linguistic approaches, among them through discourse and pragmatic analysis approaches. Furthermore, since short stories also classified as works of art (literature), so a semiotic approach can be relevant to support the approaches of discourse and pragmatics analysis. The data in this study comes from the text of a short story titled “Alun-Alun Seribu Patung” by Danarto. The data was obtained by using observation method through recording technique as a basic technique and note-taking technique as an advanced technique. Through text deconstruction, at least there are 16 derivative text constructions selected as the data which reflect the association of the short story with the political reality at the reformation and post-reformation periods (1998—2006). The description of data becomes the clues that actually the author pragmatically did a number of actions, namely reflecting, associating, predicting, evaluating, and criticizing something related to the political and natural events during the reformation and post-reformation periods.